Mapping of a mouse ribosomal DNA promoter by in vitro transcription. - Grummt, I (1981)
An in vitro transcription system that provides proper initiation of RNA polymerase I on cloned rDNA has been used to identify the start site for rDNA transcription. Different subclones that span defined regions of the 5' terminal region of the ribosomal gene have been constructed and assayed in the cell-free system for their ability to promote specific initiation of pre-rRNA synthesis. It is shown that rapid processing at the 5' end of the primary transcript occurs both in vivo and in vitro which in former studies has led to a wrong interpretation of the S1 nuclease mapping data (1 - 3). RNA polymerase I starts in vitro at a unique point on the rDNA yielding run-off transcripts that have a triphosphorylated 5' end pppApC. If multiple copies of the promoter-containing rDNA fragment were placed in head-to-tail orientation in front of the transcribed region distinct RNA products were synthesized that have been started at the tandem initiation sites. Removal of sequences upstream the initiation site indicates that 5' flanking regions are essential for specific transcription.